Drug trapping and delivery using a PANDA ring resonator - Suwanpayak, N.; Yupapin, P. P. (My University, 2011)
We propose a novel drug delivery system (DDS) by using a PANDA ring resonator to form and transmit and receive the microscopic volume by controlling some suitable ring parameters. The optical vortices (gradient optical field/well) can be generated and used to form the trapping tool in the same way as the optical tweezers. The microscopic volume (drug) can be trapped and moved (transported) dynamically within the wavelength router or network. In principle, the trapping force is formed by the combination between the gradient field and scattering photons, which has been reviewed. The advantage of the proposed system is that a transmitter and receiver can be formed within the same system, which is called transceiver, which is available for microscopic volume (drug volume) trapping and transportation (delivery).
Keywords: Drug delivery; Hybrid repeater; Hybrid transceiver; PANDA ring resonator